Reactogenicity of mRNA- and Non-mRNA-Based COVID-19 Vaccines among Lactating Mother and Child Dyads - Beth Jacob-Chow; Kandarpa Lakshmi Vasundhara; Hon Kit Cheang; Le Ye Lee; Jia Ming Low; Zubair Amin (Vaccines, 2022)
The aims of the study are to: (a) Describe the reactogenicity of WHO-approved two mRNA (Pfizer-BioNTech, Moderna) and two non-RNA (Oxford-AstraZeneca, Sinovac) vaccines among lactating mother and child pairs, and (b) Compare and contrast the reactogenicity between mRNA and non-mRNA vaccines. A cross-sectional, self-reported survey was conducted amongst 1784 lactating women who received COVID-19 vaccinations. The most common maternal adverse reaction was a local reaction at the injection site, and the largest minority of respondents, 49.6% (780/1571), reported experiencing worse symptoms when receiving the second dose compared to the first dose. Respondents reported no major adverse effects or behavioural changes in the breastfed children for the duration of the study period. Among respondents who received non-mRNA COVID-19 vaccines, a majority reported no change in lactation, but those who did more commonly reported changes in the quantity of milk supply and pain in the breast. The more commonly reported lactation changes (fluctuations in breast milk supply quantity and pain in the breast) for the non-mRNA vaccines were similar to those of respondents who received mRNA vaccines. Our study, with a large, racially diverse cohort, further augments earlier reported findings in that the COVID-19 vaccines tested in this study did not cause any serious adverse events in our population for the duration of our survey period, although long-term effects are yet to be studied.